Implementing and Monitoring the Response to Intervention Process: The Special Educator Perspective - Gates, Leigh K.; Fischetti, John C.; Moody, Amelia (Journal of the American Academy of Special Education Professionals, 2013)
As a result of the varied implementation of Response to Intervention (RTI) and uneven occurrence of professional development, special education teachers struggle to adapt to new roles and responsibilities. The purpose of this mixed methods study was to explore the role of special education teachers in implementing and monitoring RTI, the role change of special education teachers as a result of RTI, and the professional development required to support special education teachers implementing RTI. The results suggest a need for greater collaboration between general and special educators in the areas of implementation, fidelity monitoring, and professional development.